(untitled) (American Journal of Management, 2023)
We conduct a study of a large sample collected from hospitals to extend the knowledge of quality indicators in the healthcare profession and to determine if results are consistent over time. Findings show that, over time, the hospital size and teaching status were consistent indicators of higher rates of error as shown by several patient safety variables. This is contrary to conventional wisdom, which holds that the best care is provided by large teaching hospitals. As a result, context variables are shown to influence quality indicators in a healthcare setting that could also offer implications for quality in other industries.